TRANSFER TEKNOLOGI PENGOLAHAN BUAH MENJADI PRODUK KERIPIK DAN PERMEN JELLY - Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
The purpose of this community service is diversification of local fruit processed products, so that seasonal fruit can be consumed out of season in processed form. The group involved in this activity is Calikng Raya Jaya Farmers Group which is a local fruit processors and catholic women group which is a product marketers. The main training methods provided are fruit sorting techniques, fruit storage, and vacuum frying process. Also jelly sweets making process, product quality measurement, and product packaging. Product quality characteristics measured on chips are texture and also calories as nutritional information on the packaging label, while for jelly sweets are the water content. The results showed that fruit chips and jelly sweets can be used as alternatives products that have long shelf life. Processed fruit chips and jelly sweets can be used as alternative processed food that has potential as a source of income in Lingga Village, Kubu Raya Regency, West Kalimantan Province